Influencia de la Inteligencia Artificial en el Desempeño Organizacional de Empresas Industriales - Valenzuela Fourage, Luciana; Fernández García, Daniela; Valenzuela Fourage, Luciana; Fernández García, Daniela (Corporación universitaria Americana, 2026)
Introduction: This study presents a systematic literature review (PRISMA) of articles published between 2020 and 2025 on the impact of artificial intelligence (AI) on the organizational performance of industrial companies. Objectives: A recent, multidisciplinary corpus was compiled based on searches in Scopus and Web of Science, using filters for fields related to management, engineering, and social sciences, as well as language and open access. Methodology: Bibliometric analyses reveal a surge in 2023–2024 and a high degree of thematic cross-cutting. Substantively, AI acts as a catalyst for organizational transformation by reconfiguring structures and processes, optimizing data-driven decision-making, and enhancing productivity, efficiency, and sustainability. Review: The evidence also shows effects on organizational resilience and learning through automation, advanced analytics, and smart metrics. However, the positive impact depends on enabling conditions: ethical leadership, a culture of innovation, data governance, and capacity building to address resistance to change. Generative AI and hybrid intelligence amplify team creativity and performance, complementing—not replacing—human work. Conclusions: Overall, the findings confirm that AI has a significant and sustained impact on business transformation and performance when it is strategically integrated with human talent and responsible adoption frameworks.